2017
DOI: 10.1111/joor.12476
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular movements and bite force in Alzheimer's disease before and after new denture insertion

Abstract: Chewing impairment has been observed in elders with Alzheimer's disease (AD); however, it is unknown whether oral rehabilitation can improve their masticatory function. This study evaluated the influence of new removable prostheses on chewing function of patients with AD. Participants using removable dentures were divided into two groups: patients with mild AD (77·2 ± 5·8 years, n = 16) and controls (76·0 ± 4·4, n = 16). All participants received general dental treatment and new total and/or partial removable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…This finding may be explained by differences between urban and rural lifestyles, availability of medical resources and convenience of medical access [ 3 , 40 ]. Patients with AD also exhibit impairments in chewing function due to progressive neurodegeneration, increasing the risk of periodontal problems [ 41 , 42 ]. Hence, proper dental care and oral rehabilitation are necessary to improve masticatory function in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be explained by differences between urban and rural lifestyles, availability of medical resources and convenience of medical access [ 3 , 40 ]. Patients with AD also exhibit impairments in chewing function due to progressive neurodegeneration, increasing the risk of periodontal problems [ 41 , 42 ]. Hence, proper dental care and oral rehabilitation are necessary to improve masticatory function in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, many researchers found that the level of patients' satisfaction exceeded that of their dentists. [8][9][10][11][12] This finding may be due to differences in the criteria used for evaluation by the clinician and the patient. The clinicians' evaluation mainly focuses on the technical characteristics of the prosthesis, while the patients' evaluations in based on subjective criteria like appearance, function and comfort of the prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is no difference between the patients who possess the upper rather than the lower prosthesis nor between those who possess both. This result, although it is in contrast with part of the literature, can be explained by the results obtained by Campos et al .,[ 27 ] which show that adaptation to mandibular complete dentures is dependent on patients’ clinical conditions, subjective acceptance, and compliance. All the results discussed so far establish that prosthetic quality is a key element in determining clear and lasting satisfaction over time.…”
Section: Discussionmentioning
confidence: 99%